Environmental Legacies of Major Events: Solid Waste Management and the Commonwealth Heads of Government Meeting (CHOGM) in Uganda - Katusiimeh, Mescharch W.; Mol, Arthur P.J. (African Studies Quarterly, 2011)
Important political, cultural, or sports events can accelerate improvements in environmental policy and performance. This study investigates whether environmental improvements–and especially those related to solid waste–materialized during the 2007 Commonwealth Heads of Government meeting (CHOGM) in Kampala, Uganda, and whether these improvements lasted well after that event. A quantitative survey was used to investigate the state of solid waste management before, during, and after CHOGM, measured through the perceptions of urban residents. Interviews and documents were used to interpret survey results. The study concludes that additional resources and institutional changes in solid waste management in the lead up to CHOGM, resulted in considerable improvements. Some of these effects on solid waste management lasted up to at least one year after hosting the CHOGM event. In addition, CHOGM lifted the differences in perceptions of solid waste management between the city center and peripheral divisions.
Keywords: Environmental Legacies; Events; Solid Waste Management; Commonwealth Heads of Government Meeting (CHOGM)